Phase I trial of radiation therapy and sorafenib in unresectable liver metastases. Issue 2 (May 2017) - Goody, Rebecca B.; Brade, Anthony M.; Wang, Lisa; Craig, Tim; Brierley, James; Dinniwell, Robert; Wong, Rebecca K.S.; Cho, Charles; Kim, John; Kassam, Zahra; Ringash, Jolie; Knox, Jennifer J.; et al.
Abstract: Background and purpose: To determine maximum tolerated dose (MTD) and toxicities of sorafenib combined with stereotactic radiotherapy (SBRT) or whole liver radiotherapy (WLRT) in patients with liver metastases. Material and methods: Eligible patients had unresectable liver metastases. Sorafenib dose was escalated in 2 strata: I – SBRT: effective liver volume irradiated ( V eff ) < 80% (30–60 Gy in 6 fractions); II – WLRT: V eff > 80% (21.6 Gy in 6 fractions). Four weeks of sorafenib, with radiotherapy during weeks 2–3, was delivered at 3 escalating dose levels (200–400 mg twice daily). Dose limiting toxicity was defined as any grade 3+ liver toxicity, or grade 4+ treatment-related toxicity. Results: Thirty-three patients were treated: 18 in stratum I (median dose 42 Gy), 15 in stratum II. The MTD was not reached. Grade 3+ toxicity was seen in 33% of patients, at a median of 10 days. Two deaths from non-classic liver toxicity occurred post WLRT in stratum II. The median overall survival was 22.3 and 5.7 months for strata I and II respectively. Conclusions: Sorafenib and 21.6 Gy in 6 fraction WLRT resulted in unacceptably high rates of liver toxicity. Although sorafenib combined with SBRT was tolerable, the observed efficacy does not merit further clinical evaluation.